2019
DOI: 10.1002/cssc.201901058
|View full text |Cite
|
Sign up to set email alerts
|

Layered Confinement Reaction: Atomic‐level Dispersed Iron–Nitrogen Co‐Doped Ultrathin Carbon Nanosheets for CO2 Electroreduction

Abstract: High electrochemical over‐potential and low product selectivity are regarded as the main limitations of electroreduction of CO2. Here, we proposed a new strategy to synthesize metal porphyrin‐hybridized porous and ultra‐thin carbon nanosheets (MPPCN) by the confinement function of the layered template. The layered confinement reaction protects the coordination structure of metal and nitrogen atoms during subsequent high‐temperature treatment while ensuring the formation of ultra‐thin structures. This method ef… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(14 citation statements)
references
References 45 publications
0
12
2
Order By: Relevance
“…Based on the EXAFS fitting results, the Fe‐N coordination number is around four at temperatures higher than 400 °C (Table S4). The possible FeN 4 moieties have been theoretically predicted active for the CO2RR [3, 7, 48] . Unlike previous reports, [7, 49] we found that mild thermal activation is sufficient to generate active FeN 4 sites for the CO2RR.…”
Section: Resultscontrasting
confidence: 58%
“…Based on the EXAFS fitting results, the Fe‐N coordination number is around four at temperatures higher than 400 °C (Table S4). The possible FeN 4 moieties have been theoretically predicted active for the CO2RR [3, 7, 48] . Unlike previous reports, [7, 49] we found that mild thermal activation is sufficient to generate active FeN 4 sites for the CO2RR.…”
Section: Resultscontrasting
confidence: 58%
“…Interestingly, the improvement in catalytic activity by increasing dispersion of active sites owing to confinement effect has also been extended to electrocatalytic reduction of CO 2 . [45,46] Especially, Tuo e al reported a new strategy to synthesize metal porphyrin-hybridized porous and ultra-thin carbon nanosheets (MPPCN) by the confinement function of the layered template. In the preparation process, the layered confinement reaction protects the coordination structure of metal and nitrogen atoms during subsequent hightemperature treatment while ensuring the formation of ultrathin structures.…”
Section: Increasing Metal Dispersionmentioning
confidence: 99%
“…Excessive CO 2 emission form combustion of fossil fuels has caused a series of environmental problems. Electrocatalytic CO 2 reduction to value added chemicals by renewable electricity is of great significance for tackling the carbon emissions and recycle use of CO 2 …”
Section: Introductionmentioning
confidence: 99%